KOMPETENSI, LINGKUNGAN KERJA DAN KUALITAS PELAYANAN - Larbiel Hadi; Seno Andri; Zaili Rusli (Universitas Riau, 2018)
Competence, Work Environment and Service Quality. This study aims to determineand analyze the influence of competence, work environment together and partially on the qualityof service at the Faculty of Economics and Social Sciences UIN Suska Riau. This type of researchis a quantitative approach with survey methods and data analysis is quantitative / statistical. Theannouncement of primary data through a questionnaire on 98 employee respondents at the Facultyof Economics and Social Sciences UIN Suska Riau as well as secondary data throughorganizational data relating to the problem under study. Data analysis method uses Multiple LinearRegression with the help of SPSS application. The results showed that together the variables ofcompetence, work environment significantly influence the service quality of employees with fcount (77.949)> f table (3.09) and the contribution coefficient of determination (R2) is 62.1%.37.1% is influenced by other variables not examined in this study.